Poligami perspektif Rasyid Ridha: Telaah tafsir Al Manar surah An Nisa Ayat 3 - Rahma, Eka Nur (Maliki Interdisciplinary Journal, 2023)
Polygamy, a conversation that can continuously be a fascinating discussion. This is on the grounds that polygamy is where a man can wed more than one lady. So it generally raises a ton of discussion, beginning from whether families engaged with polygamy can in any case be amicable? Do ladies who are polygamous by their spouses get fair treatment? This is the thing will be talked about in this review, which will make sense of the translation of surah An-Nisa ayah 3 in regards to the reasonability and necessities of equity in polygamy. It will be talked about in light of the understanding point of view of Al Manar by Rasyid Ridha. Utilizing the scholarly strategy by breaking down a ton of writing connected with polygamy according to the understanding viewpoint of Al Manar.